Violent extremism and iconisation: commanding good and forbidding evil?. Issue 1 (1st January 2017) - Wignell, Peter; Tan, Sabine; O'Halloran, Kay L.
ABSTRACT: This study employs a multimodal social semiotic approach to the analysis of text and image relations in material produced by the violent extremist organisation known as Islamic State in Iraq and al-Sham (ISIS). The study focuses on iconisation, where meanings are condensed and interpersonally charged through 'bonding icons' which embody the organisation's world view and values. A sample of issues in the online magazine Dabiq produced by ISIS are analysed using Systemic Functional Multimodal Discourse Analysis (SF-MDA). The ISIS world view is shown to be internally cohesive, based on a narrow, fundamentalist interpretation of selected Islamic scripture and violently opposed to any other world view. To represent, synthesise and justify its values and world view, ISIS uses bonding icons constructed from combinations of artefacts, supported by references to selected Islamic scripture. The study is a prelude to more detailed investigation of bonding icons in materials produced by ISIS, the attraction of SIS to potential mujahideen and 'copy-cat' jihadist groups and the recontextualisation of materials from Dabiq in different media platforms. Such studies would provide deeper insights into the workings of organisations such as ISIS, and facilitate the further development of multimodal social semiotic approaches to image and text relations.